The Yellow Yacht - Roy, Ron 1940-; Gurney, John Steven (New York : Random House, 2005)
Dink, Josh, and Ruth Rose help catch the thieves who have stolen gold from Sammi's parents, the king and queen of Costra.
"A Stepping Stone book."
2.8.
006-009.
Keywords: Mystery and detective stories; Stealing -- Fiction; Kings, queens, rulers, etc -- Fiction